Metodologija povyšenija tocnosti peredaci mjaca svjazujušcich igrokov v processe volejbol'noj podgotovki - Umarov, K. M.; Abdurakhimov, Z. H.; Nasimov, U. A. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
This article explores the features of a volleyball player in the process of developing the accuracy of passing the ball. A pedagogical experiment was conducted on the effectiveness of passing the ball to 13-14 years old, and during the pedagogical experiment, a series of training microcycles and exercises were developed to increase the effectiveness of passing the connecting players. This set of exercises was widely used by the selected research group during the training, as a result of which the accuracy of passing the ball to the participants in the research group after the pedagogical experience was significantly increased. The analysis of the results obtained, the accuracy of the passing movements of the connecting players, the accuracy of the transmitted ball and the low altitude were reflected in the results of the experiments. It has been studied how important it is to pay special attention to the correct formation of the passing movements of the connecting players from the very beginning of the training phase, and the results of the pedagogical experiment proved to be important. During the tournament and training, the accuracy of passing the ball to the connecting players and the speed of performing tactical combinations were analyzed and recommendations were given.